Assessment of bone quality with trabecular bone score in type 2 diabetes mellitus: A study from the FRISBEE cohort. Issue 5 (17th April 2019) - Baleanu, Felicia; Bergmann, Pierre; Hambye, Anne Sophie; Dekelver, Carole; Iconaru, Laura; Cappelle, Sylvie I.; Moreau, Michel; Paesmans, Marianne; Karmali, Rafik; Body, Jean‐Jacques
Abstract: Objective: The purpose of our study was to compare bone mineral density (BMD) and trabecular bone score (TBS) values between patients with type 2 diabetes (T2D) and control subjects with similar FRAX scores in order to evaluate TBS as an additional tool for assessing fracture risk in diabetic subjects. Methods: A cross‐sectional analysis was performed using BMD results from 260 subjects participating in the FRISBEE study (Fracture RISk Brussels Epidemiological Enquiry), an ongoing prospective epidemiological study in a population‐based cohort (Brussels, Belgium) of 3560 postmenopausal women aged 60‐85 years. TBS measurement was possible in 1108 subjects from the FRISBEE cohort. Among these 1108 subjects, 65 had known T2D at inclusion. For each diabetic case we selected 3 controls from our database. (n = 195). Diabetic subjects and controls were matched for age and baseline FRAX score for major osteoporotic fractures. Results: BMD (g/cm 2 ) tended to be higher in T2D than in control subjects, significantly so at the total hip 0.90 ± 0.13 versus 0.87 ± 0.12 ( P = 0.015). On the contrary, TBS was significantly lower in the T2D group (mean = 1.19 ± 0.17) compared with the control group (mean = 1.27 ± 0.13) ( P = 0.005). Mean TBS remained significantly lower in T2D (1.22 ± 0.17) compared with the control group (1.27 ± 0.13) ( P = 0.02) after adjustment for body mass index. Conclusion: Our data suggest that TBS complements BMD at the total hip, in demonstrating the "diabetes‐associated bone disease".